The Expansion of Administrative Decision Meaning Based on Government Administration Law: a Dispute Submission Process Approach - I Gusti Ngurah Wairocana; I Ketut Sudiarta; I Wayan Bela Siki Layang; Kadek Agus Sudiarawan; I Gede Pasek Pramana (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2019)
The establishment of Government Administration Law brings significant change to the competence of the previously restricted Administrative Court to become expanded. This study aims to find the philosophical considerations from the extension of Administrative Decision meaning on Government Administration Law, to classify the legal implication arising from the regulation of the expansion of administrative decision meaning towards dispute submission process in Administrative Court and to formulate ideal attitude of the State Administrative Judge in resolving State Administrative Disputes. This is a combination of normative and empirical legal research. The study indicated that the legislator main consideration in regulating the expansion of administrative decision meaning on Government Administration Law is to expand the absolute competence of Indonesian Administrative Court which previously felt very narrow. The implication arises after new regulation consists of: the expansion of Administrative Court adjudicate authority for factual actions, subject expansion that have the authority to issue Administrative Decision, the expansion of the Administrative Court adjudicate authority over Administrative Decision which has a legal consequences although still need the approval from above instance, the regulation that Administrative Decision can be sued through the Administrative Court of any potential loss that may arise by the issuance of its Administrative Decision and the expansion towards the parties who have a chance to field a State Administrative accusation. The ideal attitude of State Administrative Judge is the judge should remain based on the strong theoretical concepts of the law so can create understanding and attitude in handling a case in Indonesian Administrative Court.